Effect of high-temperature stress on rice grain quality - Sanjeeva Rao, D; Siromani, N; Poojitha, J; Sakhare, Akshay S; Rao, P Raghuveer; Subrahmanyam, D (ORYZA-An International Journal of Rice, 2023)
High-temperature stress (HS) due to global warming has become a serious threat to global food and nutritional security. Among the various agro-morphological and physiological changes observed in rice (Oryza Sativa L.) due to high-temperature sress, yield and grain quality are highly important and they vary among the germplasm. As reports on the effect of high-temperature stress on grain quality are less, rice grown under ambient as well as high-temperature conditions were subjected to important grain quality aspects to identify the least affected rice. Twenty-five entries were cultivated in two neighboring experimental plots, one for normal and the other for high-temperature stress (HS). High-temperature stress was imposed by enclosing the field-grown crop with a transparent polyethylene sheet supported by a metal frame at the onset of the reproductive phase. Temperature inside the above structure (treatment) as well as outside (control) was recorded until the crop was harvested. The mean minimum and maximum increase in temperatures were 0.67°C and 10.2°C respectively over the ambient conditions. After harvesting, all the paddy samples of both control and treatment were dried under shade and processed to brown rice which was manually separated into chalky and normal grains on a trans-illuminator. Further, total starch and protein contents were estimated separately in the chalky and normal grains of each sample. ANOVA indicated that temperature during the reproductive stage significantly (p<0.01) influenced the starch as well as protein contents. An increase in total starch content was observed in both normal and chalky grains under high-temperature stress. The difference in total starch amongst the genotypes was significant (p<0.01), however, the differences in total starch content between normal and chalky grain under both control and high-temperature stress condition was non-significant. Although the mean protein content for all the genotypes was not significantly affected in chalky and normal grains under control, it was reduced by >5% in chalky grains under high-temperature stress. Five entries noted £10% yield loss. Of these, IET29944 appears to be less affected in multiple parameters.